Negative Reciprocity: The Coevolution of Memes and Genes - Daniel Friedman; Nirvikar Singh (University of California, Economics Department, 2003)
A preference for negative reciprocity is an important part of the human emotional repertoire. We model its role in sustaining cooperative behavior but highlight an intrinsic free-rider problem: the fitness benefits of negative reciprocity are dispersed throughout the entire group, but the fitness costs are borne personally. Evolutionary forces tend to unravel people's willingness to bear the personal cost of punishing culprits. In our model, the countervailing force that sustains negative reciprocity is a meme consisting of a group norm together with low-powered (and low-cost) group enforcement of the norm. The main result is that such memes coevolve with personal tastes and capacities so as to produce the optimal level of negative reciprocity.
Keywords: 330; Altruism; reciprocity; negative reciprocity; coevolution